Moisture Sorption Characteristics of Shrikhand at 20oC and 30oC - KHOJARE, AJIT SHANTARAMSINGH (Indian Journal of Dairy Science, 2018)
Moisture sorption characteristics of shrikhand were investigated at 20oC and 30oC using the static gravimetric method.  Sorption curves obtained were sigmoid in shape and classified as type II.  EMC values increased with increase in water activity and decreased with increase in temperature. Among the GAB, Halsey & Oswin models tested, the GAB model best fitted the EMC data obtained.  GAB model could be said to be the best model to predict the experimental moisture sorption data and to characterize the sorption behavior of shrikhand within the temperature and water activity range of study.  GAB monolayer values were 6.50 and 7.23 g H2O/100 g solids at temperature 20oC to 30oC respectively.  The appearent area of sorption decreased from   254.02 m2/g solid at 20oC to 226.97 m2/g solid at 30oC.  Density of sorbed water, number of adsorbed monolayers, percent bound and non freezable water was determined using Caurie equation. The area of adsorption of water molecules at the triple point of water was 3.785 m2/g and activation energy of first layer of water molecules in shrikhand was found to be 0.5083 J/mol. Net isosteric heat of sorption decreased with corresponding increase in moisture content, initially rapidly up to 14.79 g of water/100 g of solids and latter approached a constant value.  The entropy of sorption decreased from 81.73 J/mol K at 10.28 g H2O/100g solid to   12.72 J/mol K at 23.95 g H2O/100g solid.